2009
DOI: 10.1186/1471-2458-9-422
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the El Niño-Southern Oscillation on dengue epidemics in Thailand, 1996-2005

Abstract: BackgroundDespite intensive vector control efforts, dengue epidemics continue to occur throughout Southeast Asia in multi-annual cycles. Weather is considered an important factor in these cycles, but the extent to which the El Niño-Southern Oscillation (ENSO) is a driving force behind dengue epidemics remains unclear.MethodsWe examined the temporal relationship between El Niño and the occurrence of dengue epidemics, and constructed Poisson autoregressive models for incidences of dengue cases. Global ENSO recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
72
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 31 publications
(61 reference statements)
15
72
1
4
Order By: Relevance
“…These results suggest that the HFRS incidence dynamics are interrelated with climate change and the MEI can serve as a potential predictor of HFRS occurrence. We notice that similar results have been found for diseases like dengue fever, dengue hemorrhagic fever, hantavirus cardiopulmonary syndrome, and malaria [68][69][70][71]. Moreover, regional precipitation is known to be influenced by ENSO, showing the strongest interrelation with climate variability around the Globe [72].…”
Section: Discussionsupporting
confidence: 84%
“…These results suggest that the HFRS incidence dynamics are interrelated with climate change and the MEI can serve as a potential predictor of HFRS occurrence. We notice that similar results have been found for diseases like dengue fever, dengue hemorrhagic fever, hantavirus cardiopulmonary syndrome, and malaria [68][69][70][71]. Moreover, regional precipitation is known to be influenced by ENSO, showing the strongest interrelation with climate variability around the Globe [72].…”
Section: Discussionsupporting
confidence: 84%
“…Several previous studies that use climate to model dengue fever include an autoregressive time series component based on the idea that the current value of the time series can be explained as a function of past values (Hii et al, 2012;Tipayamongkholgul et al, 2009). However, these studies do not always quantify the contribution of an autoregressive lagged disease term compared to climate covariates to the variance explained by such a model.…”
Section: Discussionmentioning
confidence: 99%
“…That said, the tendency to store water during dry conditions may well provide suitable breeding sites for the dengue vector. In contrast to Johansson et al [61], Tipayamongkholguln et al [67], analysing dengue data for Thailand using Poisson regression, found that up to 22% (in eight northern inland mountainous provinces) and 15% (in five southern tropical coastal provinces) of the variation in the monthly incidence of dengue cases were attributable to global ENSO cycles as described by the ENSO multivariate and sea level pressure indices, with the tendency for dengue incidence to increase during El Niño phases. However, the authors noted some geographical heterogeneity in ENSO dengue associations, with not all individual provinces revealing statistically significant associations.…”
Section: Denguementioning
confidence: 98%